Analisis Kepercayaan Diri Siswa SMP terhadap Pembelajaran Matematika pada Masa Pandemi Covid-19 - Amalia; Imami, Adi Ihsan (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2021)
The purpose of this research is to find the self-confidence level of students during the Covid-19 pandemic. Students and teachers cannot interact directly during the learning process with an online learning system, which is different from the previous one, where students and teachers learn face-to-face. Therefore, the researcher wants to analyze the self-confidence level of middle school students in this pandemic. This research uses a qualitative method (descriptive), with 36 students from SMP Negeri 1 Rawamerta as subjects. Based on the results of this research, the obtained indicator percentage are: 1) belief in oneself 53,17%; 2)not giving up 47,78%; 3)not depending on others 58,33%; 4)responsible 76,39%; 5)high achiever; 6)dare to express opinions 34,03% with the average amount of 56,06%. Then it can be concluded that the self-confidence level of middle school students in seventh grade are in the category of most of them having self-confidence.